Pleistocene water intrusions from the Mediterranean and Caspian seas into the Black Sea - Badertscher S.; Fleitmann D.; Cheng H.; Edwards R. L.; Gokturk O. M.; Zumbuhl A.; Leuenberger M.; Tuysuz O. (Springer Science and Business Media LLC, 2011)
The hydrological balance of the Black Sea is governed by riverine input and by the exchange with the Mediterranean Sea. A speleothem record from a cave in northern Turkey that tracks the isotopic signature of Black Sea surface water suggests an open connection to the Mediterranean Sea in at least twelve periods in the past 670,000 years.